Business Strategy Through Understanding Characteristics and Planning Concepts - Rohmah, Ainnur; Dwi Nur Aini; Halimatus Sa'diyah; Mailani Amriatul Aulia; Nunuk Indarti (International Journal of Technology and Education Research, 2026)
Business planning is a crucial process that determines the direction, goals, and strategic steps needed to run a business effectively and efficiently. Good planning must be based on accurate data, realistic analysis, clear objectives, and the ability to adapt to changes in the business environment. Through thorough planning, business owners can identify opportunities, predict risks, prepare alternative strategies, and optimize resource utilization. Furthermore, business planning serves as a guideline for decision-making, a performance evaluation tool, and a means of strengthening trust with external parties such as investors and partners. With structured planning, operational activities can run more effectively, competitiveness increases, and the prospects for business success are enhanced. Overall, business planning provides a strategic foundation for business sustainability and growth.